Light grazing of saltmarshes is a direct and indirect cause of nest failure in Common Redshank Tringa totanus. (2nd March 2015) - Sharps, Elwyn; Smart, Jennifer; Skov, Martin W.; Garbutt, Angus; Hiddink, Jan G.
Abstract : The Common Redshank Tringa totanus breeding population on British saltmarshes has declined by over 50% since 1985, with declines linked to changes in grazing management. Conservation initiatives have encouraged low‐intensity grazing of less than one cattle per hectare, but Redshank have continued to decline, even in regions where light grazing was predominant. This study quantified effects of grazing intensity on Redshank nest survival over six lightly grazed saltmarshes with livestock densities between 0 and 0.82 cattle per hectare, in the Ribble Estuary, northwest England. We assessed whether grazing resulted in nest mortality directly through cattle trampling and/or indirectly through grazer modification of habitat that accelerates predation risks. Cattle density was recorded both during the Redshank breeding season and for 1 year prior to the study, to account for both short‐term trampling effects and the longer term effects on vegetation. Results showed that risk of nest loss to trampling increased from 16% at 0.15 cattle per hectare to 98% at 0.82 cattle per hectare in the breeding season. The risk of a nest being predated increased from 28% with no grazing to 95% at 0.55 cattle per hectare based on all year grazing data. These results suggest that even light conservation grazing at less than one cattle per hectare can reduce Redshank nest survival rates to near zero. It may therefore be appropriate to reduce saltmarsh grazing intensities, or change the timing of saltmarsh grazing to reduce the number of livestock present during the Redshank breeding season.